Heavy Metal Ions Removal From Wastewater Using Cryogels: A Review - Türkmen, Deniz; Bakhshpour, Monireh; Akgönüllü, Semra; Aşır, Süleyman; Denizli, Adil (Frontiers in Sustainability, 2022)
Water contamination by heavy metal pollution is induced by rapid industrialization and urbanization. Removal of heavy metal ions from wastewater is of prime importance for a clean environment and human health. The heavy metal problem is seriously threatened to human health. In addition, these metals are toxic and carcinogenic. They cause serious problems for aquatic ecosystems and especially humans. Different methods have been utilized to remove heavy metals from the wastewater, such as membrane filtration, adsorption, and ion exchange. Adsorption is one of the most efficient processes to clean contaminated water. The adsorption process presents advantages such as availability, low cost, and eco-friendly nature. The commercial adsorbents and the polymeric adsorbents are showed a high removal capacity for heavy metal ions capturing and removing from wastewater. Several researchers have widely used cryogels as a unique bio-adsorbent for heavy metals removal from wastewaters. Cryogels are efficient for the removal of heavy metal ions. This manuscript comprehensively and critically reviews current research in heavy metal adsorption by cryogels that prepared various technology and highlights the main advantages of these materials. Cryogels are synthetic polymers used in adsorption experiments in recent years. Because of their macropores, they provide an excellent advantage as an adsorbent in continuous and batch adsorption processes. The process applied for cryogel formation is called cryogelation. These macroporous gel matrices can be produced with different shapes and the gels are of interest in the bioseparation area since they can meet needs that conventional chromatographic media are less suitable to fulfill. The structure, synthesis, and composition of various cryogels are presented. Cryogels are generally synthesized by bulk polymerization under semifrozen conditions at -12 °C and 18 °C for 12 to 24 hours. The cryogels have a high removal capacity rate of over 90%. In the cryogels based studies, Fourier transforms infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), thermal, surface area, elemental, and computerized microtomography (μCT) analyses can be used for the characterization of cryogels structure.